SISTEM TRACKING REPORT BERBASIS WEBSITE PADA PT CARDIG INTERNATIONAL SUPPORT - Betesda Betesda; Jehan Saptia Kurmia (JSI (Jurnal Sistem Informasi) Universitas Suryadarma, 2024)
PT.Cardig International Support Textile Industry is  having problems,  the total lead time  delays due to the  production process because  of  no system  that  can  track and  report  stages of  the  production  process. Thus  requiring  a report tracking system  that can resolve the  production process of the  problem. The method  used is  an experimental method to design an information system by using uml diagrams to design object and php-mysql programming language for application creation. Results from this study is the creation of a tracking system application reports that the production process can reduce total lead time delay process production and can trace and report stages of production occurring so as to know which processes are having problems or experiencing delays. The control method for all existing orders is sufficient to meet the demand for product delivery times (Delivery On Time) to customers and the facilities used to control all existing orders are sufficient to support and optimal in their use, and the Tracking Report system can help overcome Lead Time and Delivery On Time problems.